Eksplorasi Komunikasi Ritual dalam Merajut Partisipasi serta Kerukunan Masyarakat Desa Adat Penglipuran - Tiaraningrum, Agnesia Hervina (Universitas Pahlawan Tuanku Tambusai, 2025)
Independent village development by Penglipuran Traditional Village combines cultural sustainability with sustainable development, maintaining local heritage and understanding of local values which is the key in maintaining authenticity and sustainability in Penglipuran Traditional Village. The research aims to explore the experience of ritual communication as a form of participation and harmony of the Penglipuran Traditional Village community which has local traditions that have been passed down from generation to generation and ancestral beliefs about the social order of the community, togetherness, and kinship in community life in harmony. This research was obtained qualitatively by using ethnographic studies through reality in an informative manner through the stages of interviews, direct observation and becoming participants. Based on the results and discussion of the process of participation of customary villages through ritual communication, it was concluded that the process of participation was fully running well. With the participation of indigenous peoples, it can be increased by interpreting a tradition. As a result of the latest data findings, rituals that are believed by the community are an influence on the integrity and maintenance of the community system so that the community actively participates.